2018
DOI: 10.1002/jcp.27102
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor γ modulates renal crystal retention associated with high oxalate concentration by regulating tubular epithelial cellular transdifferentiation

Abstract: The differentiated phenotype of renal tubular epithelial cell exerts significant effect on crystal adherence. Peroxisome proliferator‐activated receptor γ (PPARγ) has been shown to be critical for the regulation of cell transdifferentiation in many physiological and pathological conditions; however, little is known about its role in kidney stone formation. In the current study, we found that temporarily high oxalate concentration significantly decreased PPARγ expression, induced Madin Darby Canine Kidney cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…The HK-2 cell line exposed to calcium oxalate presents increased TGF-β1 production, decreased expression of epithelial and increased mesenchymal markers, and significant mesenchymal changes, migration, and invasiveness [21]. Similar results were observed in vitro in the CaOx-exposed Madin-Darby canine kidney (MDCK) cell line, supporting the evidence for EMT in kidney stone disease [20].…”
Section: Epithelial-to-mesenchymal Transition (Emt)supporting
confidence: 69%
See 2 more Smart Citations
“…The HK-2 cell line exposed to calcium oxalate presents increased TGF-β1 production, decreased expression of epithelial and increased mesenchymal markers, and significant mesenchymal changes, migration, and invasiveness [21]. Similar results were observed in vitro in the CaOx-exposed Madin-Darby canine kidney (MDCK) cell line, supporting the evidence for EMT in kidney stone disease [20].…”
Section: Epithelial-to-mesenchymal Transition (Emt)supporting
confidence: 69%
“…Epithelial-to-mesenchymal transition (EMT), which plays an important role in processes such as inflammation, cancer, and fibrosis, is phenotypical transformation of epithelial cells in which cell-cell adhesion, morphological characteristics and polarity weaken while invasiveness and cell migration increases. This process could also be induced by oxalate crystals, most likely by activation of TGF-β1 and the Notch/Snail pathway [19,20].…”
Section: Epithelial-to-mesenchymal Transition (Emt)mentioning
confidence: 99%
See 1 more Smart Citation
“…It modulates gene expression by binding to peroxisome proliferator response element (PPRE) sites and affects the transcription of downstream target genes [10]. Li et al demonstrated that the PPAR- γ agonist 15-deoxy- Δ 12,14-prostaglandin J2 (15d-PGJ2) can prevent CaOx stone formation both in vivo and in vitro [11]. However, the mechanism of PPAR- γ signaling in oxalate-induced tubular cell injury requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Oxalate-induced ROS production is considered to be the result of TGF- β 1 activation [17]. Recently, multiple studies have suggested that PPAR- γ agonists can exert a therapeutic effect on kidney disease by inhibiting TGF- β 1 signal transduction [11]. PPAR- γ agonists can inhibit TGF- β 1 mRNA and protein expression [7].…”
Section: Introductionmentioning
confidence: 99%